The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1155/2021/8889313
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Matrix Metalloproteinase‐9 Protects against Sepsis‐Induced Acute Lung Injury via Promoting the Release of Soluble Receptor for Advanced Glycation End Products

Abstract: Dysregulation of matrix metalloproteinase- (MMP-) 9 is implicated in the pathogenesis of acute lung injury (ALI). However, it remains controversial whether MMP-9 improves or deteriorates acute lung injury of different etiologies. The receptor for advanced glycation end products (RAGE) plays a critical role in the pathogenesis of acute lung injury. MMPs are known to mediate RAGE shedding and release of soluble RAGE (sRAGE), which can act as a decoy receptor by competitively inhibiting the binding of RAGE ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
4
11
0
Order By: Relevance
“…Etiologies such as sepsis were implicated in the activation of the RAGE-dependent NF-kB signaling cascade associated with inflammatory processes and oxidative stress [ 75 ]. Zhang H et al reported that MMP9 mediated the shedding of RAGE , and might exacerbate sepsis-associated pulmonary inflammation by controlling RAGE/NF-κB signaling [ 76 ]. MMP9 is also considered to be a macrophage gene [ 77 ], where its overexpression in the lung tissue of septic mice model correlates with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Etiologies such as sepsis were implicated in the activation of the RAGE-dependent NF-kB signaling cascade associated with inflammatory processes and oxidative stress [ 75 ]. Zhang H et al reported that MMP9 mediated the shedding of RAGE , and might exacerbate sepsis-associated pulmonary inflammation by controlling RAGE/NF-κB signaling [ 76 ]. MMP9 is also considered to be a macrophage gene [ 77 ], where its overexpression in the lung tissue of septic mice model correlates with our study.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is one of the key enzymes involved in the production of sRAGE. MMP9-mediated sRAGE production inhibited the RAGE/NF-κB activation and consequently reduced the severity of pulmonary edema, inflammation, and oxidative stress ( Zhang et al, 2021 ). During SARS-CoV-2 infection, patients showed increased expression of MMP9 compared to controls ( Gelzo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the extracellular domain of RAGE is cleaved by the metalloproteinases ADAM10 and metalloprotease 9 (MMP9), and the extracellular segment of RAGE is released, forming soluble RAGE (sRAGE) ( Metz et al, 2012 ). sRAGE acts as a decoy and binds to RAGE ligands, reducing RAGE activation ( Zhang et al, 2021 ). These processes form an elegant negative-feedback loop to contain RAGE concentrations and activation, and control the extent of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, ROS contribute to the damage of the epithelial barrier. ROS-dependent induction of the matrix metalloproteinase (MMP)-9 causes damage, internalization, and downregulation of proteins of intercellular connections, so-called tight junctions [ 150 ], such as claudins, occludins, and E-cadherins, linking the extracellular glycocalyx with the intracellular cytoskeleton ( Figure 4 a) [ 151 , 152 ]. The loss of cell–cell interactions consequently is associated with an increase in permeability and gap formation [ 117 ], leading to edema formation [ 153 ].…”
Section: Methodsmentioning
confidence: 99%